Thermo‐mechanical behavior of stretch‐broken carbon fiber and thermoplastic resin composites during manufacturing. Issue 4 (24th March 2014) - Wang, Peng; Hamila, Nahiène; Boisse, Philippe; Chaudet, Philippe; Lesueur, David
Abstract : Stretch‐broken fiber reinforcements and thermoplastic resin commingled prepregs are interesting for manufacturing composite parts in aeronautic and automobile industries. With these materials it is possible to produce composite parts with complex geometries, and high curvatures. On the other hand the length of the fibers leads to mechanical properties of the final composite that are close to those of the composite with continuous fibers. This paper analyzes the thermo‐mechanical properties of Stretch Broken Carbon Fiber (SBCF) / PPS and PEEK commingled prepregs during manufacturing. Tensile and in‐plane shear tests at different temperatures are analyzed. The experiments are realized in an isothermal oven. The range of temperature is those of the part during a thermoforming process. The experimental data allow to analyze the differences on the tensile and in‐plane shear behaviors at different temperatures between thermoplastic prepregs with continuous fibers and thermoplastic prepregs with stretch‐broken fibers. Forming simulations show that wrinkling can be avoided with SBCF prepregs while these wrinkles develop during continuous fibers prepreg forming. POLYM. COMPOS., 36:694–703, 2015. © 2014 Society of Plastics Engineers